”Analisis Jabatan” Studi Efektivitas kerja pada SDM Karyawan Universitas Muhammadiyah Lampung berdasarkan deskripsi jabatan dan spesifikasi jabatan - Adzlan Syah, Tansri; Nurhayati, Any (Innovative: Journal Of Social Science Research, 2023)
Human Resources (HR) management has become a crucial thing. In fact, the members of the organization are the most important influencing factor because their behavior will facilitate or hinder the achievement of the organization in the long term. Job analysis is the process of developing job duties from a position and employee requirements that are appropriate to fill the initial position. This qualitative research used primary and secondary data. The subjects were 101 structural employees of Universitas Muhammadiyah Lampung. Job analysis prepares job descriptions and job specifications. Job Analysis helps influence the work quality of Universitas Muhammadiyah Lampung employees because it really helps employees in carrying out their duties and completing tasks as well as their job specifications.